Penguatan Wawasan Kebangsaan Sebagai Strategi Pendidikan Moderasi Beragama di Era Revolusi Industri 4.0 - Khoirus Shobri; Nanang Abdillah (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
In the era of the Fourth Industrial Revolution, the development of Information and Communication Technology (ICT) has transformed the way we understand and practice religion, including the spread of extremist religious ideologies. Religious moderation education has become an essential tool for strengthening national awareness by instilling values of tolerance, inclusivity, and love for the homeland. This education promotes a balanced and tolerant understanding of religion. However, a significant challenge arises from the overwhelming flow of information on the internet, which is not matched by adequate digital literacy. Therefore, religious moderation education serves as a filter to counter radicalization. This study uses a review research method with a qualitative approach to analyze the implementation of religious moderation education through formal, nonformal, and informal channels. The findings indicate that formal education is effective in instilling moderate character through a systematic structure. Nonformal institutions, such as Islamic boarding schools and study groups, also play a crucial role in spreading moderate Islamic values. Meanwhile, informal education within families provides a vital foundation for instilling these values from an early age. This study recommends strengthening the religious moderation curriculum, optimizing the role of nonformal institutions, and empowering families to enhance national awareness and address the potential for radicalization.